PEMANFAATAN BAHAN PUSTAKA DALAM MENINGKATKAN PRESTASI BELAJAR SISWA ( STUDI PADA PERPUSTAKAAN SMK NEGERI 1 WANGI-WANGI, KABUPATEN WAKATOBI) - Al Aziz Al Aziz (Jurnal Ilmu Komunikasi UHO : Jurnal Penelitian Kajian Ilmu Komunikasi dan Informasi, 2016)
ABSTRACT  The problems raised in this research is how the use of the material libraries in improving student achievement (studies at the library of SMKN 1 Wangi-wangi, the district of wakatobi), and what are the constraints affecting students in the use of library material to improve student achievement in the library of SMKN 1 Wangi-wangi. This study aims to know the use of material libraries in improving student achievement (studies at the library of SMKN 1 Wangi-wangi, the district of wakatobi), and to know the constraints affecting students in the use of library material to improve student achievement in the SMKN 1 Wangi-wangi. The number of informants in this study is 8 (eight) people. Determination informant done by using purposive sampling technique (deliberately), the informant selected on the basis of consideration that the informant that can provide accurate information and clear based research purposes. the data was collected via library study and field research then analyzed descriptive qualitative that describe the results based findings in the field and then given interpretation and conclusions by using the sentence logically. these results indicate that the use of the material libraries in improving student achievement (studies at the library of SMKN 1 Wangi-wangi, the district wakatobi), among others, read, spend time, learning or add science, searching information in the complete the task is given by teachers, and borrow book.  keywords: use of the material libraries, learning achievement.